Expert Systems with Applications in the Legal Domain. (2015) - Cornelia, Ana-Maria; Murzea, Cristinel Ioan; Alexandrescu, Bogdan; Repanovici, Angela
Abstract: The most controversial aspect of the collaboration between computer science and legal sciences remained for about two decades trying to develop programs capable of simulating specific work of a lawyer or judge. An electronic platform will be designed, a new tool for prisoners, lawyers and economic environment. Information retrieval system will be different, the DSpace open source information system will be used, will be in touch with legislative database.